Career Counseling Implementation Model - Handayani, Suri; Asra, Yulita Kurniawaty (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
This research aims to provide an overview or reveal how the career counseling model is implemented. The method used in this research is literature study. Literature study is the process of deepening, reviewing and identifying knowledge contained in the literature (reading sources, reference books or other research results) that is related to the problem being studied. Based on the research that has been carried out, the results obtained are that the model for implementing career counseling consists of several structures, namely: (1) outlining the goals or identification of client problems, clarification and opening; (2) collect client information; (3) understand and hypothesize client behavior; and (4) client goals or problem resolution. In implementing career counseling, the reasons why clients come to a career counselor, whether or not it is necessary to use psychometric questionnaires or other questionnaires as well as gender, cultural and developmental psychology perspectives in relation to individual careers. The researcher hopes that this research can add insight and contribute knowledge about how to implement career counseling models so that the implementation of career counseling carried out by counselors can run smoothly and be successful in achieving its goals.